TRANSFORMASI NILAI-NILAI DAN ALAM PEMIKIRAN WAYANG BAGI MASA DEPAN JATI DIRI BANGSA INDONESIA - Soeprapto, Sri; Jirzanah, Jirzanah (Jurnal Filsafat "WISDOM", 2009)
AbstractWayang becomes one of evidences of Indonesians history in a cultural transformation. Wayang stories become more various by the Hindu’s stories influences which are Ramayana and Mahabharata. Both of Hindu’s stories influence on creating newwayang stories, but the old stories are not discarded.A thought about grandeur values of human life with its excellence and weakness symbolizes three choices of valueshierarchy of the wayang story. First, matter values concerningabout worldly pleasure. Second, spiritual values, they are truth,goodness, and beauty values. Three, religious values, they areholiness and eternity values. A consideration based on the needs of values hierarchy and way of thinking is that a modernization process does not need to eliminate the roles of spiritual and religious values. Religious values are brought into being sources of reference to settle life problems. Spiritual values are kept being put in a hierarchy which is more glorious than worldly values. An urgent problem in the framework of developing nation identity is the ideal type of Indonesian in the future. The ideal type of Indonesian should has three dimensions: bio individual, social organizational, and theological dimension.Keyword: Wayang, values hierarchy, modernization.